2009
DOI: 10.1159/000198245
|View full text |Cite
|
Sign up to set email alerts
|

Der Magenballon – eine retrospektive Kohortenanalyse mit 634 Patienten

Abstract: Hintergrund: Der temporÄre Einsatz eines Magenballons zur Behandlung der Adipositas Grad1 und 2 nimmt weltweit zu; bei der Adipositas Grad 3 wird der Magenballon als adjuvantes Hilfsmittel zur prÄoperativen Gewichtsreduktion implantiert. Ziel dieser retrospektiven Kohorten analyse ist, die Wirksamkeit des Magenballons auf Gewichtsreduzierung und das Risikoprofil der Methode zu evaluieren. Methoden: Retrospektive Kohortenanalysen aus 4 Adipositas-Zentren, in denen der Magenballon seit 2001 regelmÄßig implantier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In a large multicenter study, Genco et al (76) showed that the use of BIB induced a significant reduction of BMI and an improvement of comorbidities. Indications for BIB usage in lower degrees of obesity have been increasingly accepted (74,77), and the improvement in metabolic profile after the BIB placement has been reported in several studies (75,(78)(79)(80)(81)(82)(83).…”
Section: Intragastric Balloonmentioning
confidence: 99%
“…In a large multicenter study, Genco et al (76) showed that the use of BIB induced a significant reduction of BMI and an improvement of comorbidities. Indications for BIB usage in lower degrees of obesity have been increasingly accepted (74,77), and the improvement in metabolic profile after the BIB placement has been reported in several studies (75,(78)(79)(80)(81)(82)(83).…”
Section: Intragastric Balloonmentioning
confidence: 99%
“…Early experiences with endoluminal gastroplasty indicate its viability in obesity treatment [40, 41]. Novel endoscopic tools perform gastric plicating/partitioning with sutures (Bard EndoCinch Suturing System (C.R.…”
Section: Introductionmentioning
confidence: 99%
“…Balloons are increasingly used for the temporary treatment of obesity grades I and II. The method is also a preoperative treatment for obesity grade III [30, 41]. Intragastric balloon is an appropriate therapeutic tool for patients who aim to lose above 10% of their initial body weight and need to be assisted while adopting new eating and behavioral habits [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation